Vascular Permeability Factor/Vascular Endothelial Growth Factor Induces Lymphangiogenesis as well as Angiogenesis - Nagy, Janice A. (The Rockefeller University Press, 2002)
Vascular permeability factor/vascular endothelial growth factor (VPF/VEGF, VEGF-A) is a multifunctional cytokine with important roles in pathological angiogenesis. Using an adenoviral vector engineered to express murine VEGF-A(164), we previously investigated the steps and mechanisms by which this cytokine induced the formation of new blood vessels in adult immunodeficient mice and demonstrated that the newly formed blood vessels closely resembled those found in VEGF-A–expressing tumors. We now report that, in addition to inducing angiogenesis, VEGF-A(164) also induces a strong lymphangiogenic response. This finding was unanticipated because lymphangiogenesis has been thought to be mediated by other members of the VPF/VEGF family, namely, VEGF-C and VEGF-D. The new “giant” lymphatics generated by VEGF-A(164) were structurally and functionally abnormal: greatly enlarged with incompetent valves, sluggish flow, and delayed lymph clearance. They closely resembled the large lymphatics found in lymphangiomas/lymphatic malformations, perhaps implicating VEGF-A in the pathogenesis of these lesions. Whereas the angiogenic response was maintained only as long as VEGF-A was expressed, giant lymphatics, once formed, became VEGF-A independent and persisted indefinitely, long after VEGF-A expression ceased. These findings raise the possibility that similar, abnormal lymphatics develop in other pathologies in which VEGF-A is overexpressed, e.g., malignant tumors and chronic inflammation.